2020
DOI: 10.37616/2212-5043.1040
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure In The Middle East Arab Countries: Current And Future Perspectives

Abstract: For many years, data about heart failure (HF) was only limited to Western countries but in the last few years, well designed heart failure registries have been conducted in many developing countries. The purpose of this review is to summarize the current status regarding the epidemiology and management of heart failure in Middle East Arab countries (MEACs) by analysis of the results of the latest HF registries performed in these countries and to anticipate future perspectives, quality initiatives and areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 19 publications
2
48
1
Order By: Relevance
“…Data has shown that the average age of individuals with HF is at least 10 years younger than their Western counterparts, so this is a sign that heart failure is known to be a disease of the elderly, but when the mean age of incidence is in the late fifties to early sixties, then it is not a disease of the elderly in the Middle East; it is instead a disease of middle to old age population. (Elasfar et al, 2020). This age information was consistent in all registries done for heart failure in Arab countries.…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…Data has shown that the average age of individuals with HF is at least 10 years younger than their Western counterparts, so this is a sign that heart failure is known to be a disease of the elderly, but when the mean age of incidence is in the late fifties to early sixties, then it is not a disease of the elderly in the Middle East; it is instead a disease of middle to old age population. (Elasfar et al, 2020). This age information was consistent in all registries done for heart failure in Arab countries.…”
Section: Introductionsupporting
confidence: 76%
“…The estimated population in this region is 250 million, and the global prevalence of HF is 1-2%, so we estimate 3.75 million patients with HF in this region. (Elasfar et al, 2020). Data has shown that the average age of individuals with HF is at least 10 years younger than their Western counterparts, so this is a sign that heart failure is known to be a disease of the elderly, but when the mean age of incidence is in the late fifties to early sixties, then it is not a disease of the elderly in the Middle East; it is instead a disease of middle to old age population.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations